Kepuasan Tamu Tentang Breakfast Di Royal Restaurant Grand Royal Denai Hotel Bukittinggi - Indah Septiani Putri; Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Abstract. The purpose of this study is to determine the level of guest satisfaction when breakfast at the Royal Restaurant of Grand Royal Denai Hotel Bukittinggi. This type of research is quantitative descriptive research. The sampling technique used is purposive sampling with 90 people as sample. Data collection techniques are carried out by distributing questionnaires using a Likert scale that has been tested for validity and reliability. The data were analyzed through data tabulation and descriptive data using percentages. The results of the study found that guest satisfaction about breakfast at the Grand Royal Denai Hotel Bukittinggi was in the category of satisfaction 90% and the category very satisfied 10%.